Contribuições do estágio supervisionado remoto presentes em memoriais de vivências - MARTINS, Thaiana Raiol (2023)
The transformations that occurred with the advance of the coronavirus, which causes the disease called COVID-19, caused several changes, reaching various areas of society, be it economic, social and even the educational area. In education, social isolation and the suspension of face-to-face teaching activities made it necessary to adopt remote teaching, as a measure of social distancing, thus challenging schools and universities to adapt to the new context. In this perspective, the present study aims to reflect on the importance of supervised internship in the training of science teachers and to identify contributions expressed in the memorials of the supervised internship experience during remote teaching based on content analysis. It concludes by the importance of affectivity and research in teacher training, as well as the need to start approaching the reality of schools to methodologies that use information and communication technologies.